Impact of rs174537 on Critically Ill Patients with Acute Lung Injury: A Secondary Analysis of the OMEGA Randomized Clinical Trial. Issue 10 (14th September 2020) - Dosso, Beverly; Waits, Charlotte Mae K; Simms, Kelli N; Sergeant, Susan; Files, D Clark; Howard, Timothy D; Langefeld, Carl D; Chilton, Floyd H; Rahbar, Elaheh
ABSTRACT: Background: Nutrition in the intensive care unit is vital for patient care; however, immunomodulatory diets rich in PUFAs like γ-linolenic acid (GLA), EPA, and DHA remain controversial for patients with acute respiratory distress syndrome. We postulate that genetic variants impacting PUFA metabolism contribute to mixed responses to PUFA-rich diets. Objectives: In this study, we aimed to test the effects of single nucleotide polymorphism (SNP) rs174537 on differential responses to PUFA-rich diets. Methods: We performed a secondary analysis of the OMEGA trial (NCT00609180) where 129 subjects received placebo control diets and 143 received omega-oil. DNA was extracted from buffy coats and used to genotype rs174537; plasma was used to quantitate PUFAs. We tested for SNP–diet interactions on PUFA concentrations, inflammatory biomarkers, and patient outcomes. Results: We observed that all individuals receiving omega-oil displayed significantly higher concentrations of GLA, EPA, and DHA (all P < 0.0001), but they did not vary by genotype at rs174537. Statistically significant SNP–diet interactions were observed on circulating DHA concentrations in African Americans. Specifically, African American T-allele carriers on placebo illustrated elevated DHA concentrations. Additionally, all individuals receiving omega-oil had higher concentrations of EPA-derived urinary F3-isoprostane (Caucasians: P = 0.0011; African Americans: P = 0.0002). Despite these findings, we did not detect any significant SNP–diet interactions on pulmonary functional metrics, clinical outcomes, and mortality. Conclusions: This study highlights the importance of genetic and racial contributions to PUFA metabolism and inflammation. In particular, rs174537 had a significant impact on circulating DHA and urinary isoprostane concentrations. Given our relatively small sample size, further investigations in larger multiethnic cohorts are needed to evaluate the impact of rs174537 on fatty acid metabolism and downstream inflammation. Abstract : This study reveals new insights on the impact of rs174537 on differential responses to omega-rich diets, and inflammation in patients with acute lung injury or acute respiratory distress syndrome (ARDS). rs174537 was associated with altered levels of circulating DHA and urinary isoprostanes in ARDS patients.